Nomophobia and its impact on mindfulness and self-efficacy among nurses: An analytical cross-sectional study in the institution of national importance, Western India - Karitika Sharma; Aashish Parihar; Suresh K. Sharma; Naresh Nebhinani; Irasangappa B. Mudakavi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The interaction between people and advanced information and communication technologies results in behavioral addictions, one of them is nomophobia. In a health care setting, nurses constitute a significant proportion of healthcare workers. Therefore, discovering the level of nomophobia and its impact on constructs such as mindfulness and self-efficacy is very important as this might affect the psychological and physical well-being of nurses, which can impact the quality of patient care. The study aimed to assess the level of nomophobia and its relationship with mindfulness and self-efficacy of nurses. METHODS AND MATERIAL: An analytical cross-sectional study was carried out in a tertiary care hospital. A total of 420 nurses were selected using a convenience sampling technique. Self-structured questionnaire was used to assess socio-demographic characteristics and mobile phone use. Standardized questionnaires were administered in pen and paper format for measuring nomophobia, mindfulness, and self-efficacy. Statistical Package for Social Sciences (SPSS) version 20.0 was used. Karl Pearson's correlation coefficient and Chi-square test were employed to analyze the data. RESULTS: The majority of nurses (99.5%) had nomophobia. About half of them (53.3%) had a moderate level of nomophobia. Nearly half of nurses had high level of mindfulness (52.6%) and self-efficacy (53.3%) respectively. Further, nomophobia was found to be negatively correlated with mindfulness (r = -0.289) and self-efficacy (r = -0.278). CONCLUSION: Nomophobia poses a risk to the mindfulness and self-efficacy of nurses. Continuing education should focus on awareness programs emphasizing good practices in the use of current technologies.